Nursing Care for Neurological System Disorders on Carotid Infarction Stroke Through the Provision of Mirror Therapy Intervention - Widiawati; Farhan, Zahara (CV. Literasi Publikasi Indonesia, 2025)
Stroke infarction is a condition caused by an interruption in blood supply to the brain due to blockage, leading to loss of motor and sensory functions. This results in limb weakness, which impacts daily activities. Mirror therapy is a rehabilitative intervention involving the neuronal system to improve muscle strength in stroke patients with limb weakness. This study aims to evaluate the application of mirror therapy as a nursing intervention to enhance muscle strength in infarction stroke patients. Using a case study approach, data were collected through anamnesis, observation, physical examination, and medical records. Four nursing problems were identified: physical mobility disorders, verbal communication disorders, self-care deficits, and risk of falling. Mirror therapy was employed as the primary intervention for physical mobility disorders. Despite four days of therapy at a frequency of once per day, no significant improvement in muscle strength was observed in the patient with hemiparesis due to infarction stroke. It is recommended that mirror therapy be implemented over a longer duration and frequency for optimal results in nursing practice